MODEL PEMBELAJARAN TREFFINGER BERBANTU APLIKASIWORDWALL TERHADAP KEMAMPUAN PEMECAHANMASALAH MATEMATIS PESERTA DIDIKDI SMA N1 AIR BATU - Nuraini; Muthia Dewi (Smart Education, 2026)
The aims of this study is to determine the effect of the Treffinger Learning model assisted by the Wordwall application on the mathematical problem-solving abilities of students at SMA N 1 Air Batu. This study is a quasi-experimental study with a Two Group Pretest-Posttest Design. The population in this study was the entire tenth grade, consisting of five classes. The sample consisted of two classes (Xth-1 and Xth-2) selected using cluster random sampling. Xth-1 class served as the control class using the conventional learning model, while Xth-2 class served as the control class using the Treffinger Learning model. After the instruction is completed, a posttest is conducted, showing the average results for the experimental 53,793 and control classes 40,459. The t-test results tcount = 8,057>ttable=2,003 so Ho is rejected and H1 accepted, indicating the influence of the Treffinger Learning model assisted by the Wordwall application on the mathematical problem-solving abilities of students at SMA N 1 Air Batu.